2021
DOI: 10.7717/peerj.11389
|View full text |Cite
|
Sign up to set email alerts
|

A review of sourdough starters: ecology, practices, and sensory quality with applications for baking and recommendations for future research

Abstract: The practice of sourdough bread-making is an ancient science that involves the development, maintenance, and use of a diverse and complex starter culture. The sourdough starter culture comes in many different forms and is used in bread-making at both artisanal and commercial scales, in countries all over the world. While there is ample scientific research related to sourdough, there is no standardized approach to using sourdough starters in science or the bread industry; and there are few recommendations on fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 149 publications
(426 reference statements)
1
31
0
Order By: Relevance
“…In this work, we assessed the differences in nutritional and organoleptic quality between breads made with eight different leavening agents and two different wheat flours. Previous studies also compared sourdough and yeast breads [ 6 , 7 , 8 , 9 , 10 , 11 ]. The originality of this work is that type I sourdoughs were used, two wheat varieties were tested, and real artisanal hand-made bread-making processes were carried out, with a total fermentation time of five hours on average.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we assessed the differences in nutritional and organoleptic quality between breads made with eight different leavening agents and two different wheat flours. Previous studies also compared sourdough and yeast breads [ 6 , 7 , 8 , 9 , 10 , 11 ]. The originality of this work is that type I sourdoughs were used, two wheat varieties were tested, and real artisanal hand-made bread-making processes were carried out, with a total fermentation time of five hours on average.…”
Section: Discussionmentioning
confidence: 99%
“…Sourdough strains of S. cerevisiae have been shown to be generally different from commercial strains of S. cerevisiae both genetically and phenotypically when analysed in laboratory conditions [ 5 ]. However, to our knowledge, no studies have compared the effect of sourdough and commercial yeast fermentation and wheat varieties on both organoleptic and nutritional quality of bread in traditional bakery conditions [ 6 , 7 , 8 , 9 , 10 , 11 ]. Da Ros et al compared a laboratory-made sourdough bread with a yeast bread and showed that sourdough enhanced the synthesis of short-chain fatty acids and gamma amino butyric acid.…”
Section: Introductionmentioning
confidence: 99%
“…Indisputably, very encouraging results have been obtained by the exploitation of different types of sourdoughs, which have been used as natural bread-leavening agents since antiquity. Sourdough confers many advantages onto bread, such as improved nutritional value, health benefits, sensory characteristics, and shelf-life [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sourdough is a complex mixture of lactic acid bacteria (LAB) and yeasts. Yeasts are responsible for the leavening activity of sourdough, while LAB contribute to ameliorated shelf-life, texture, and sensorial properties of bread through the production of various organic acids, antimicrobial metabolites, and texture conditioners [ 6 , 7 , 8 ]. Furthermore, some LAB may exhibit health-promoting properties such as antitumor, antioxidant, and anti-inflammatory properties [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since ancient times, sourdough has been used as a natural leavening agent in bread production and shared among artisanal bakers and home-baking communities. Commonly, sourdoughs are classified into four types [2]:…”
Section: Introductionmentioning
confidence: 99%